Faktor-faktor yang Memengaruhi Kesejahteraan Petani Padi di Jawa Timur: Sebuah Analisis Regresi Linier Berganda - Anggaraeni, Meirisa; Zainuddin, Ahmad; Suwandari, Anik; Rahman, Rena Yunita (Universitas Galuh, 2025)
This research aims to determine: (1) Trends in grain price fluctuations in 2024-2025; (2) Factors that influence farmer welfare. The research area was determined deliberately (purposive method), where this research used monthly data on the price of dry harvested grain in 2018-2022 in East Java. The research methods used are descriptive and analytical. The data collection method used in the research is secondary data from trusted sources such as the Central Statistics Agency (BPS), aligned articles and books. The data analysis method to determine the trend of grain price fluctuations in East Java is exponential smoothing analysis using multiple linear regression analysis. The results of this research show that: (1) The trend in grain prices in 2023-2025 fluctuates and tends to increase. In the three-year forecast period, the highest average price of grain will be in 2025, namely IDR 5,207, which is due to the increasing demand for rice; (2) The variables of grain price, production, land area and labor wages together influence the welfare of rice farmers in East Java. The variables of grain price and labor wages have a positive and significant effect on farmer welfare with significance values of 0.000 and 0.006 respectively. The land area variable has a positive and insignificant effect on farmer welfare with a significance value of 0.599. Production variables has a negative and insignificant effect on farmer welfare with a significance value of 0.229.